Cortisol Hormone Concentration and Meat Quality of Beef Cattle Stunned by Captive Bolt Stun Gun before Slaughtering - K Maghfiroh; H Latif; K Santoso (Media Peternakan, 2014)
This study was aimed to describe cortisol hormone concentration and meat quality which were produced in beef cattle stunned with captive bolt stun gun before slaughtering. Blood and meat samples were taken from Brahman cross steers (n= 11) in two abattoirs located in West Java and Banten. Blood samples were collected immediately after slaughtering. Cortisol hormone concentration in the serum was measured by using radioimmunoassay (RIA). The descriptive, correlation, and regression analyses were used to interprete data. Meat quality assessment was based on pH, cooking loss, and complete drainage of blood. The average of cortisol hormone concentration was 26.59 ng/mL. Meat pH at 1 h postmortem and 24 h postmortem were 6.65 and 6.21, respectively. Meat cooking loss was 26.77%. Blood drainage in meat samples of each cattle showed complete drainage. There was a significant correlation (P<0.05) between cortisol concentrations and pH at 1 hour postmortem as well as cortisol concentration and cooking loss. There was no significant correlation between pH at 24 h postmortem and cooking loss. Cattle was stunned with a captive bolt stun gun before slaughtering produced meat with complete blood drainage but had high cortisol hormone concentration and pH ultimate. Key words: cortisol, quality of meat, stunning, captive bolt stun gun